Public journalism connecting with the community - Evelio B. Javier Foundation ([Manila] Evelio B. Javier Foundation, 2001)
Documentary showcases public journalism initiatives among community journalists in various parts of the Philippines.
Narration in English with some interviews in Filipino.
VCD.
Keywords: Journalism, Rural -- Philippines; Mass media -- Moral and ethical aspects -- Philippines; Mass media and social service -- Philippines; Mass media in community development -- Philippines